2002
DOI: 10.1590/s0034-89102002000200003
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade em idosos por diabetes mellitus como causa básica e associada

Abstract: OBJETIVO:Analisar a mortalidade por diabetes mellitus em idosos e a subenumeração do diabetes como causa do óbito de acordo com estatísticas baseadas unicamente em causa básica de óbito. MÉTODOS:Foram revisadas todas as 2.974 declarações de óbito ocorridas em 1994 de idosos residentes em um núcleo habitacional localizado na cidade do Rio de Janeiro, RJ. Destas, foram estudados 291 óbitos, tendo o diabetes mellitus como causa básica (150) e associada (141). A proporção de óbitos em que a diabetes aparece como c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
(1 reference statement)
0
3
0
16
Order By: Relevance
“…Mortality figures underestimate the burden of diabetes, since the underlying cause of death (including diabetes) is not accounted in the final cause of death estimates. Coeli et al [19] examined 2,974 death certificates of older adults and found that 291 subjects had diabetes as one of the reported causes of death. However, only 150 subjects had diabetes as the underlying cause of death.…”
Section: Resultsmentioning
confidence: 99%
“…Mortality figures underestimate the burden of diabetes, since the underlying cause of death (including diabetes) is not accounted in the final cause of death estimates. Coeli et al [19] examined 2,974 death certificates of older adults and found that 291 subjects had diabetes as one of the reported causes of death. However, only 150 subjects had diabetes as the underlying cause of death.…”
Section: Resultsmentioning
confidence: 99%
“…Em estudo realizado no Rio de Janeiro, compreendendo 2.974 óbitos de indiví duos de 60 anos ou mais, o diabetes foi mencionado em 9,8% das declarações e, entre os óbitos por diabetes, 51,5% haviam sido classificados como causa básica (32). Em outro estudo (33), foi analisado o conjunto (3.872) de declarações de óbito do ano 2000 do município de Niterói, Rio de Janeiro, observando-se menção de diabetes em 313 (8,1%).…”
Section: Discussionunclassified
“…Improvements in health care programs and a decrease in tobacco consumption have most likely influenced a decline in the rates of stroke in recent decades [1,5]. Diabetes has affected mortality as an associated cause, although deaths directly attributable to diabetes have remained relatively stable in recent decades [1,6]. Diabetic patients in Brazil have a more than three-fold excess mortality rate compared to the general population [7,8] and, as in other settings, most of this excess mortality is driven by increased cardiovascular mortality risk [7].…”
Section: Introductionmentioning
confidence: 99%